THE IMPACT OF FRIENDSHIP CIRCLE ON MENTAL HEALTH OF SEMARANG STATE UNIVERSITY STUDENTS - Octiva, Ambar; Husain, Fadly (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
This research aims to determine the importance of social circles for mental health. The method used in this study is a qualitative approach through case study, employing interview techniques and observations with 8 informants from various faculties at Universitas Negeri Semarang. The results obtained from this research revealed two categories: the impact of social circles on mental health and the lack of impact of social circles on mental health. Among the eight informants, three were found to have social circles that significantly influenced their mental health, while five informants had social circles that did not significantly impact their mental health.